Peran Transparansi Informasi Dalam Memoderasi Pengaruh Agresivitas Pajak Dan Profitabilitas Terhadap Nilai Perusahaan - Rahma, Alivia Putri; Pernamasari, Rieke; Tarmidi, Deden (Universitas 17 Agustus 1945 Jakarta, 2023)
This study aims to determine wheter there is an effect of Tax Aggressiveness and Profitability on Firm Value with Transparency as a moderating variable. The population in the study were companies listed of 10 State-Owned Enterprises (BUMN) which are listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The sampling technique used purposive sampling method and data used in this reserach is secondry data. The data analysis used moderated regression analysis (MRA) test using SPSS statistic 25. The results of this study indicate that tax aggressiveness and Profitability have no effect on firm value, transparency can moderate effect of tax aggressiveness and profitability on firm value